(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article presents a comparative investigation of the gallant paradigms and social values reflected in Uzbek and English people legends, particularly looking at Alpomish from Uzbek writing and Beowulf from English writing. Society sagas serve as basic stories that not as it were tell the stories of incredible heroes but moreover offer significant bits of knowledge into the values, standards, and social character of the social orders from which they develop. By analyzing these two seminal works, the article investigates how the depiction of valor, ethical ethics, and the relationship between the saint and society varies over these societies. Subjects such as boldness, devotion, and the fight between great and fiendish are investigated, whereas too highlighting the impact of social setting on the forming of the hero’s travel. Through this comparative approach, the article points to reveal both widespread characteristics of courage and particular social expressions in society writing, advertising modern viewpoints on how these legends proceed to resound with their particular gatherings of people.